Vocational High School Students Mathematical Communication: Auditory, Visual, and Kinesthetic Learners - Mayang Purbaningrum; Wahyu Setyaningrum (Didaktik Matematika, 2023)
Mathematical communication skills are essential in activating students' problem-solving abilities and activating excellent cognition. This study aims to analyze the mathematical communication skills conceived by vocational students on financial mathematics material according to auditory, visual, and kinesthetic learning styles. The study used descriptive qualitative with nine samples determined using a purposive sampling technique. Each learning style category comprised three quick, moderate, and slow students comprehending the given materials. The data were collected using a mathematical communication test and a learning style questionnaire. The obtained data were analyzed using Miles and Huberman's model. The results showed that students with an auditory learning style whose ability to comprehend material was quick and slow could complete mathematical communication indicators. In contrast, students with a moderate category could not complete the fourth indicator. Visual learners with quick material comprehension did not formulate situations mathematically, and all the categories did not comply with the fourth indicator. Kinesthetic learners with quick material comprehension could not complete the first and third indicators. The kinesthetic learner with slow comprehension could not fulfill the fourth indicator, while one in the moderate category could complete all mathematical communication indicators.